I IMPLEMENTASI NILAI-NILAI ANTI KORUPSI MELALUI STRATEGI INTERNALISASI KARAKTER MAHASISWA - Delna Kurniati (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Corruption remains a systemic "social parasite" that has plagued human civilization since ancient times, as evidenced by historical records from Ancient Egypt, Babylon, and Rome, as well as the long history of dynasties and colonial rule in Indonesia. In the modern era, the eradication of corruption requires more than just legal prosecution; it demands a fundamental shift in cultural paradigms and moral integrity. This study explores the implementation of anti-corruption values through internalization strategies aimed specifically at university students, who serve as "agents of change" and the future leaders of the nation.Drawing from historical perspectives and the evolution of anti-corruption legislation in Indonesia—spanning from the Old Order and New Order to the Reform Era—this research emphasizes that corruption in Indonesia is deeply rooted in opportunistic characters formed during the royal and colonial periods. To break this cycle, Higher Education institutions play a strategic role in fostering a "culture of integrity." The internalization strategy focuses on embedding nine core anti-corruption values: honesty, independence, responsibility, courage, simplicity, care, discipline, justice, and hard work.The implementation process involves integrating Anti-Corruption Education (PAK) into the academic curriculum, not merely as theoretical knowledge but as a practical guide for daily behavior. The benefits of this internalization are threefold: developing individual competence to resist corrupt personal gains, empowering students to warn others against unethical practices, and providing them with the analytical skills to identify and report corruption to legal authorities.